Understanding Use Behavior in Mobile Banking: An Extended of UTAUT Perspective - Rahmiati Rahmiati; Perengki Susanto; Alizar Hasan; Vera Pujani (AFEBI Management and Business Review, 2022)
Mobile banking is a service provided by banks to provide value and convenience to both banks and customers. However, the successful implementation of mobile banking largely depends on how much customers are fully motivated to adopt it. Thus, this study recognizes the need to examine the factors that could predict the use of mobile banking and how using such a system could contribute to increasing the intensity of use of mobile banking by customers. The conceptual model of this study uses extended UTAUT2, including price value, hedonic motivation, and habit. Data collection was carried out through a questionnaire survey by 137 respondents. Partial least square-structural equation modeling (PLS-SEM) was employed for analyzing the data. The study showed that behavioral intention and habit are significantly and positively influenced by hedonic motivation. Meanwhile, use behavior is significantly and positively influenced by habit and behavioral intention. Nonetheless, price value was found to have a negative and insignificant impact on behavioral intention to use mobile banking. The conclusion derived from this study enhances the understanding of the factors determining the use of mobile banking in West Sumatra.